Technological development of functional egg products by an addition of n-3 polyunsaturated-fatty-acid-enriched oil. Issue 2 (2nd April 2016) - Lamas, A.; Anton, X.; Miranda, J.M.; Roca-Saavedra, P.; Cardelle-Cobas, A.; Rodriguez, J.A.; Franco, C.M.; Cepeda, A.
Abstract : Eggs are good candidates to be employed as functional food and to provide people with bioactive compounds such as n-3 PUFAs. However, in most cases, development of eggs with high content of n-3 PUFAs was carried out by modifying the hens' feed. In the present work, egg-derived sticks with high content of n-3 PUFAs were technologically developed through addition of three different sources of n-3 PUFAs: linseed oil, fish oil and microalgae oil. The developed products were compared to conventional egg-derived products for their proximate composition, fatty acid profile, colour and consumer acceptability. Additionally, lipid oxidation was investigated after 30 days of frozen storage. Nutritional composition, colour parameters and consumer acceptability revealed that egg-derived product obtained by addition of linseed oil was the most adequate. Egg-derived functional foods developed by technological methods are viable and could be considered as an interesting alternative, especially for catering companies.